Implementation of maternal death audits and changes in maternal health care in Cambodia, 2010–2017 - Tung, Rathavy; Kim, Rattana; Mathai, Matthews; Cheang, Kannitha; Sobel, Howard L (Western Pacific Surveillance and Response, 2024)
Objective: Cambodia is one of seven countries globally that met Millennium Development Goal 5A: reduction of maternal deaths by at least 75% between 1990 and 2015. To support improving maternal care, the Maternal Death Audit (MDA) was instituted in 2004. This report highlights changes in maternal health services and MDA implementation in Cambodia between 2010 and 2017. Methods: International experts and the national MDA Committee assessed all case abstracts, investigation questionnaires and audit meeting minutes covering all maternal deaths reported in Cambodia in 2010 and 2017 for quality of classification, data, care and recommendations. They convened provincial MDA committees to conduct similar assessments and develop evidence-informed recommended actions. Results: In 2010 and 2017, 176 and 59 maternal death cases were reported, respectively. Cases were more likely in 2017 than in 2010 to have antenatal care (90.0% vs 68.2%, P = 0.004), give birth in a facility (81.6% vs 55.3%, P = 0.01) and receive a prophylactic uterotonic (95.7% vs 73%, P < 0.05) for postpartum haemorrhage (PPH) and magnesium sulfate (66% vs 37%, P = 0.18) for pre-eclampsia/eclampsia. However, additional interventions and improved timeliness of referral with equipped and competent staff were identified as critical. Data quality prevented classifying one-fourth of cases during both periods. MDA recommendation quality improved from 2.8% in 2011 to 42% in 2018. Discussion: Improvements in maternal care are reflected in the increased antenatal care, facility births and better PPH and preeclampsia-eclampsia management. However, additional care management improvements are highlighted. The MDA reporting needs improved data completeness and more specific recommendations to address causes of death.